BODY IMAGE, TINGKAT KECUKUPAN ZAT GIZI, DAN FAD DIETS PADA MODEL REMAJA PUTRI DI SURABAYA [Body Image, Nutritional Adequacy Level, and Fad Diets among Female Adolescent Models in Surabaya] - Imas Nur Jannah; Lailatul Muniroh (Media Gizi Indonesia, 2019)
Female adolescent models are required to look attractive which could trigger a negative body image and rapid weight loss by involving fad diets. This study was aimed to analyze the relationship between body image and nutritional adequacy level with fad diets among female adolescent models in Surabaya. This study was a cross sectional on 60 female adolescent models aged 14-20 who were selected by accidental sampling technique. Nutritional adequacy level was assesed using food recall 2x24 hours, body image and fad diets were evaluated using modified Body Shape Questionnaire (BSQ-16a) and fad diets questionnaire. Data were analyzed by chi square test. The results showed that most female adolescent models had negative body image (58.3%); energy adequacy level (80.0%), carbohydrate (86.7%), protein (56.7%), and fat (56.7%) were categorized deficient; doing fad diets (70,0%). There were moderate correlation between body image and fad diets (r=0.484) and there was a weak correlation between energy adequacy level (r=0.054), carbohydrate (r=0.188), protein (r=0.090), and fat (r=0.232) with fad diets. It was concluded female adolescent models who had a negative body image tend to do fad diets. Female adolescent models are expected to have a healthy diet and balanced nutrition, also consult to nutritionist in order to achieve an ideal body weight.